Perspectivas y límites de la justicia global y el cosmopolitismo democrático (2013)
ABSTRACT: This paper discusses some of the proposals existing in the contemporary debate about justice. In the first part, John Rawls’ theory of justice at the international level is presented. In the second part, Jürgen Habermas’ human rights approach is presented along with a discussion questioning the arguments advanced by these authors to oppose the cosmopolitan idea of a transformation of the international order on the basis of the demands of global economic justice. Finally, the last part shows the limits and views of Thomas Pogge’s global justice proposal.